A case of successful surgical treatment of a ruptured giant aneurysm of the infrarenal aorta in an elderly patient - A. E. Zotikov; M. R. Khokonov; K. Kh. Eminov; A. M. Solovieva; A. V. Kozhanova; V. S. Ostapenko; A. Yu. Shchedrina; E. V. Chebotareva; D. L. Likalter; A. Yu. Molchanova; L. A. Aleksanyan; O. N. Tkacheva («REMEDIUM GROUP» Ltd., 2021)
Today, abdominal aortic aneurysm surgery is a fairly well-studied area of medicine. Nevertheless, some questions remain rather debatable. No clear criteria for giant aneurysms have been developed so far. The available foreign and domestic literature reports about 40 cases of surgical treatment of giant abdominal aortic aneurysms, 16 of which are cases of aneurysm rupture. Open surgery remains the method of choice in the treatment of giant aneurysms due to the pronounced technical difficulties of endovascular intervention. The authors present a case of successful surgical treatment of a giant aneurysm rupture in an elderly patient. The peculiarity of this patient's condition is the occurrence of aneurysm rupture after hospital admission. The patient refused surgical treatment for two years after aneurysm detection. On examination after admission, multispiral computed tomography revealed an aneurysm size of 101 mm. On the eve of surgery, pain syndrome in the left abdomen and tachycardia appeared. Aneurysm rupture was suspected and the patient was urgently admitted to the operating room. The surgery was performed under the conditions of machine reinfusion of autoblood. The patient underwent abdominal aortic aneurysm resection with linear prosthesis and retroperitoneal hematoma removal. The postoperative period had no peculiarities. On the 10th day after the operation the patient was discharged in satisfactory condition to the outpatient treatment. This clinical case demonstrates the possibility of successful surgical treatment of giant aneurysm rupture in elderly patients.